Bruising in children who are assessed for suspected physical abuse. Issue 2 (16th September 2013) - Kemp, Alison Mary; Maguire, Sabine Ann; Nuttall, Diane; Collins, Peter; Dunstan, Frank
Abstract : Objective: To describe the characteristics of bruising and mode of presentation of children referred to the paediatric child protection team with suspected physical abuse (PA), and the extent to which these differ between the children where abuse was confirmed and those where it was excluded. Design: Cross-sectional study. Setting and patients: 519 children, <6 years, referred to two paediatric child protection teams. Main outcome measures: The mode of presentation, number, anatomical distribution, size and appearance of bruises according to whether PA was confirmed or excluded. ORs with 95% CI were calculated where relevant. Results: PA was confirmed in 69% of children; the rate varied from 84% when abuse was witnessed, admitted, alleged or where explanation for injury was absent or implausible, to 50% where there was a concerning history. Significantly more children with PA had bruises (89.4%) than PA-excluded (69.9%) and had significantly more sites affected (p<0.001). The odds of a PA child having bruising to: buttocks/genitalia (OR 10.9 (CI 2.6 to 46), left ear (OR 7.10 (CI 2.2 to 23.4), cheeks (Left (OR 5.20 (CI 2.5 to 10.7), Right OR 2.83 (CI 1.5 to 5.4)), neck (OR 3.77 (CI 1.3 to 10.9), trunk (back (OR 2.85 (CI 1.6 to 5.0) front (OR 4.74 (CI 2.2 to 10.2), front of thighs (OR2.48 (CI 1.4 to 4.5) or upper arms (OR 1.90 (CI 1.1 to 3.2) were significantly greater than in children with PA-excluded. Petechiae, linear or bruises with distinct pattern, bruises in clusters, additional injuries or a child known to social services for previous child abuse concerns were significantly more likely in PA. Conclusions: Features in the presenting history, the extent and pattern of bruising differed between children with confirmed PA and those where abuse was excluded. These findings can provide a deeper understanding of bruising sustained from PA.